Individual, familial and country-level factors associated with oral hygiene practices in children: an international survey - Heba Mohamed Elkhodary; Mohamed Hussein Abdelnabi; Amal Ali Swelem; Heba Jafar Sabbagh; Omar Abd El Sadek El Meligy; Iman Mamdouh Talaat; Enas B. Abdellatif; Yousef Khader; Ola B. Al-Batayneh; Nuraldeen Maher Al-Khanati; Nazik M. Nurelhuda; Sara Alhabli; et al. (BMC, 2023)
Abstract Background Maintaining good oral hygiene is key to preventing dental caries and periodontal disease. Children and adolescents with good oral hygiene behaviours are likely to grow into adults with the same behaviours. This study assessed the frequency of using various oral hygiene methods among children and adolescents from different countries and individual, familial and country-level factors associated with the use of these methods. Methods A multi-country online survey collected data from caregivers of children in 2020-21 about children's use of oral hygiene methods including toothbrush, fluoridated toothpaste, mouthwash, dental floss and miswak using self-administered, close-ended questions. Adjusted multilevel logistic regression models were used to assess the relationship between each of the five oral hygiene methods (dependent variables) and the independent factors: sex, age, and history of dental visits (individual factors), mother's education and area of residence (familial factors) as well as country income and region (country-level factors). Results A total of 4766 parents/caregivers were included from 20 countries (77.4% Eastern Mediterranean-region and 41.6% lower middle income countries). The most frequent oral hygiene methods were using toothbrush and toothpaste (90% and 60.3%). The use of oral hygiene methods differed by age, sex and history of dental visits as well as mother's education and area of residence (P < 0.05). In addition, children from low income countries had significantly lower odds of using mouthwashes and dental floss than those from high income countries (AOR = 0.55, 95% CI 0.31, 0.98 and AOR = 0.34, 95% CI 0.12, 0.97) whereas children from the European region had higher odds of using mouthwash (AOR = 2.82, 95% CI 1.27, 6.26) and those from the region of the Americas had higher odds of using dental floss (AOR = 3.84, 95% CI 1.28, 11.52) than those from the Eastern Mediterranean region. Conclusions The use of various oral hygiene methods is associated with individual, familial and country-level factors. Oral health promotion programs should be developed taking into account these influences.